Syntheses, structures and magnetic properties of tetranuclear cubane-type and heptanuclear wheel-type nickel(ii) complexes with 3-methoxysalicylic acid derivatives. Issue 26 (22nd June 2017) - Kobayashi, Fumiya; Ohtani, Ryo; Teraoka, Saki; Kosaka, Wataru; Miyasaka, Hitoshi; Zhang, Yingjie; Lindoy, Leonard F.; Hayami, Shinya; Nakamura, Masaaki
Abstract : Three mono- and multi-nuclear Ni(ii ) compounds were synthesised and investigated. Abstract : Two ferromagnetic multinuclear Ni(ii ) clusters, [Ni4 L 1 4 (μ3 -OMe)4 (CH3 OH)4 ] (1 ) and [Ni7 (HL 2 )6 (μ3 -OMe)6 ]Cl2 (2 ), and a mononuclear complex [NiL 3 ]·2H2 O (3 ) (HL 1 = benzyl 2-hydroxy-3-methoxybenzoate; H2 L 2 = 1-(2-hydroxy-3-methoxybenzamido)-2-(benzylideneamino)ethane; H2 L 3 = 1-(2-hydroxy-3-methoxybenzamido)-2-(pyridylmethyleneamino)ethane) were synthesised, and their structures and magnetic behaviours were investigated in detail.1 has a [Ni4 O4 ] cubane structure while2 has a wheel-like [Ni@Ni6 ] arrangement. The temperature-dependent magnetic susceptibilities for1 and2 are in accord with the presence of dominating intra-cluster ferromagnetic interactions between Ni(ii ) ions. The best fits for their behaviours gave the following parameters: J 1 = 11.06 cm −1, J 2 = 1.43 cm −1, g = 2.29 for1, and J 1 = 6.87 cm −1, J 2 = −3.41 cm −1, g = 2.24 for2 .